Grassroots Resistance and Informal Communication Practices During the Implementation of PPKM at Baron Beach - Ardaffa Firezha Wirandika; Budi Setiyono; Dewi Erowati (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study examines community resistance to the implementation of the PPKM policy, with a focus on the tourism sector in the Baron Beach Area of Gunungkidul Regency. Using a descriptive qualitative approach, data collection involves in-depth interviews and documentation techniques. Data analysis follows a systematic process of reduction, presentation, and conclusion. The findings reveal that the complex interplay of economic, social, and political factors drives community resistance. Resistance is expressed through subtle actions, including covert discussions on social media platforms, informal community gatherings, and strategic adaptations to policy requirements. These actions exemplify 'everyday resistance,' where individuals navigate power dynamics through nuanced forms of communication and collective action. Furthermore, the study highlights the role of both formal and informal communication channels in mediating resistance, such as online forums, community newsletters, and word-of-mouth exchanges. By examining these dynamics, this research offers insight into how communities negotiate and respond to policy implementation.